2013
DOI: 10.1159/000354782
|View full text |Cite
|
Sign up to set email alerts
|

Head Injury Incidence and Mortality in New Zealand over 10 Years

Abstract: Background: Although reducing the burden of head injuries is an important focus of several injury prevention initiatives, they remain a large proportion of injury-related deaths. In New Zealand, trends over time and the socio-economic distribution of the cause-specific incidence of head injuries have received little attention. Methods: We analyzed primary hospitalizations (2000-2009) and deaths (1999-2008) due to head injury using national mortality and hospital discharge databases, specifically exploring vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
8
8
0
Order By: Relevance
“…According to the estimate of National Spinal Cord Injury Statistical Center, the annual incidence of spinal cord injury was approximately 54 cases per one million people in the USA, in which the leading causes were vehicle crashes and falls [31]. A study carried out in New Zealand showed that head injuries remained a large proportion of injury-related deaths [26]. Besides, our results of body regions of injuries basically consistent with those of Zhao Meitao.…”
Section: Differences In Cce Consumption In Different Age Groups Withsupporting
confidence: 83%
See 1 more Smart Citation
“…According to the estimate of National Spinal Cord Injury Statistical Center, the annual incidence of spinal cord injury was approximately 54 cases per one million people in the USA, in which the leading causes were vehicle crashes and falls [31]. A study carried out in New Zealand showed that head injuries remained a large proportion of injury-related deaths [26]. Besides, our results of body regions of injuries basically consistent with those of Zhao Meitao.…”
Section: Differences In Cce Consumption In Different Age Groups Withsupporting
confidence: 83%
“…The probable reason was that people in different age groups were vulnerable to different injuries. Mostly caused by falls, there were high rates of head injury admissions to hospitals occurred among 0-4-year-old (215.5 per 100,000) and people over 65 years of age (188.5 per 100,000) annually [26]. These ndings were consistent with the international mainstreams of opinions.The World Health Organization (WHO) reports that most deaths from falls happen in those aged 65 and older.…”
Section: Differences In Cce Consumption In Different Age Groups Withsupporting
confidence: 79%
“…This is in concordance with the studies conducted in many developing as well as developed nations. 1,2,[17][18][19][20][21][22][23][24][25]…”
Section: Discussionmentioning
confidence: 99%
“…Head injuries are a global public health problem, especially among children, causing significant morbidity and mortality . Head injuries impact the social, cognitive and emotional development of children, and often result in ongoing support needs for the child and their family .…”
Section: Introductionmentioning
confidence: 99%
“…The most common mechanisms that cause head injuries in children are falls, road traffic crashes and sports activities, which are all preventable. Numerous safety measures have been introduced with the aim of reducing head injuries among children, including air bags, seat belt height adjusting booster seats and rear facing infant car seats, helmets, impact attenuating playground surfaces and trampoline safety enclosures .…”
Section: Introductionmentioning
confidence: 99%